Prevalence of physical activity and its associated sociodemographic factors among schoolchildren in Albania - Brizida Refatllari; Jonida Stefa; Migena Hysa; Grejd Hyska; Gentiana Qirjako; Genc Burazeri (Healthcare in Low-resource Settings)
Physical activity (PA) promotes health and wellbeing of children. Our objective was to assess the prevalence and the associated sociodemographic factors of PA among schoolchildren in a Southeastern European country. This was a cross-sectional study conducted in Albania in 2022 including a nationwide representative sample of 5454 schoolchildren aged 11-15 years (≈52% girls; ≈96% response). Data on children’s PA and their sociodemographic factors were collected. Daily moderate-to-vigorous PA was more prevalent in boys, younger children and those from wealthier families (overall: ≈29%). Conversely, sedentary behaviour (moderate-to-vigorous PA ≤2 days/week) was more prevalent in girls, older children, rural children, those with unemployed parents and children from less affluent families (overall: ≈26%). Frequent vigorous PA (≥3 days/week) was more prevalent in boys, younger children and those from better-off families (overall: ≈64%). Our findings highlight potential advantages of PA engagement linked to both male gender and a higher socioeconomic status. This study underscores the need for targeted interventions to promote active lifestyles in children, particularly among groups at higher risk of sedentary behaviour which correspond to girls and disadvantaged socioeconomic categories.